Fully Solution Processed Pure α-Phase Formamidinium Lead Iodide Perovskite Solar Cells for Scalable Production in Ambient Condition - Yang, Fu; Dong, Lirong; Jang, Dongju; Tam, Kai Cheong; Zhang, Kaicheng; Li, Ning; Guo, Fei; Li, Cong; Arrive, Charline; Bertrand, Mélanie; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Energy Materials, 2020)
Manufacturing commercially viable perovskite solar cells still requires appropriate low-temperature and scalable deposition processes to be developed. While α-phase FAPbI3 has higher thermal stability and broader absorption than MAPbI3, there still is no report of a pure α-phase FAPbI3 perovskite film obtained by a scalable printing method. Moreover, spontaneous conversion of the α-phase to non-perovskite δ-phase under ambient conditions poses a serious challenge for practical applications. Herein, a scalable and fully solution based printing method for the fabrication of pure α-phase FAPbI3 perovskite solar cells is reported. Through adding N-methyl pyrrolidone and methylammonium chloride to the dimethylformamide based precursor solution to control the crystallization, and vacuum or air-flow assisted film drying, pure α-FAPbI3 phase is obtained by doctor blading. The resulting α-FAPbI3 film is highly stable, with no δ-FAPbI3 phase being formed even after keeping it in an ambient atmosphere over a period of 200 days without encapsulation. In addition, a fully solution processed PSC with a PCE of 16.1% is processed by the vacuum assisted method, and 17.8% by the air-flow assisted method. Replacing silver with a printed carbon electrode provides a stable PCE up to 15% for the vacuum assisted and 16.4% for the air-flow assisted method, which is the highest performance of FAPbI3 solar cells to date. Compared with MAPbI3, the fully printed FAPbI3 perovskite devices exhibit a remarkable thermal stability in humid atmospheres which makes them a promising candidate for scalable production and commercialization.
CRIS-Team Scopus Importer:2020-10-02
Keywords: carbon electrodes; doctor blades; fully printed devices; long-term stability; α-FAPbI